2023
DOI: 10.3390/buildings13123100
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing the Relationship between Compressive Strength and Modulus of Elasticity in Concrete with Ladle Furnace Slag

Víctor Revilla-Cuesta,
Roberto Serrano-López,
Ana B. Espinosa
et al.

Abstract: The addition of Ladle Furnace Slag (LFS) to concrete modifies its compressive strength and modulus of elasticity and consequently impacts their relationship. This research evaluated both properties at 28, 90, and 180 days in concrete mixes produced with 5%, 10%, and 20% of two LFS types, both stabilized and non-stabilized. The relationship between them was then analyzed through these experimental results by adopting a statistical approach. A three-way analysis of variance revealed that both properties were aff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 60 publications
0
1
0
Order By: Relevance
“…Hence, it is critical to frequently examine the mechanical properties of concrete products in the compressive mode. In addition to the destructive compression test, many empirical approaches have been recently developed to estimate the mechanical strength of concretes [4][5][6][7][8]. However, it is found that the empirical models are typically restricted to certain strength values or specified concrete compositions.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, it is critical to frequently examine the mechanical properties of concrete products in the compressive mode. In addition to the destructive compression test, many empirical approaches have been recently developed to estimate the mechanical strength of concretes [4][5][6][7][8]. However, it is found that the empirical models are typically restricted to certain strength values or specified concrete compositions.…”
Section: Introductionmentioning
confidence: 99%